A randomized trial of specialized versus standard neck physiotherapy in cervical dystonia. (February 2016) - Counsell, Carl; Sinclair, Hazel; Fowlie, Jillian; Tyrrell, Elaine; Derry, Natalie; Meager, Peter; Norrie, John; Grosset, Donald
Abstract: Background: Anecdotal reports suggested that a specialized physiotherapy technique developed in France (the Bleton technique) improved primary cervical dystonia. We evaluated the technique in a randomized trial. Methods: A parallel-group, single-blind, two-centre randomized trial compared the specialized outpatient physiotherapy programme given by trained physiotherapists up to once a week for 24 weeks with standard physiotherapy advice for neck problems. Randomization was by a central telephone service. The primary outcome was the change in the total Toronto Western Spasmodic Torticollis Rating (TWSTR) scale, measured before any botulinum injections that were due, between baseline and 24 weeks evaluated by a clinician masked to treatment. Analysis was by intention-to-treat. Results: 110 patients were randomized (55 in each group) with 24 week outcomes available for 84. Most (92%) were receiving botulinum toxin injections. Physiotherapy adherence was good. There was no difference between the groups in the change in TWSTR score over 24 weeks (mean adjusted difference 1.44 [95% CI -3.63, 6.51]) or 52 weeks (mean adjusted difference 2.47 [-2.72, 7.65]) nor in any of the secondary outcome measures (Cervical Dystonia Impact Profile-58, clinician and patient-rated global impression of change, mean botulinum toxin dose). Both groups showed large sustained improvements compared to baseline in the TWSTR, most of which occurred in the first four weeks. There were no major adverse events. Subgroup analysis suggested a centre effect. Conclusion: There was no statistically or clinically significant benefit from the specialized physiotherapy compared to standard neck physiotherapy advice but further trials are warranted. Highlights: The Bleton specialized physiotherapy technique is sometimes used in cervical dystonia. We compared this with standard neck physiotherapy in a randomized trial in 110 people. There was no difference in any primary or secondary outcome between the two groups. The Bleton technique cannot be recommended over standard neck physiotherapy. Further trials of physiotherapy for cervical dystonia are required.